2019
DOI: 10.1017/s0030605318001436
|View full text |Cite
|
Sign up to set email alerts
|

Determining the risk of predator attacks around protected areas: the case of Bardia National Park, Nepal

Abstract: In this study we determined the probability of predator attacks on livestock around Bardia National Park, Nepal. We conducted semi-structured interviews to explore the patterns and factors affecting livestock losses in four administrative sectors of the Park's buffer zone. We developed models to investigate the overall probability of livestock loss, economic damage caused, and the respondents’ attitudes towards wildlife. The probability of leopard attacks on livestock was much higher (85% of all livestock lost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 59 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…The study by Sharma et al (2020a) identified crucial factors for HWC in the Kanchenjunga landscape, with distance to road, elevation, livestock density, and mean annual temperature as good predictors. In contrast, Upadhyaya et al (2020) emphasized the importance of livestock numbers, ethnic groups, and village distance from the park boundary for explaining livestock losses in Bardia National Park, Nepal. Likewise, Sijapati et al (2021) found that common leopard-induced livestock kills in Bardia National Park were more prevalent at locations distant from the park boundary, subject to seasonality.…”
Section: Discussionmentioning
confidence: 98%
“…The study by Sharma et al (2020a) identified crucial factors for HWC in the Kanchenjunga landscape, with distance to road, elevation, livestock density, and mean annual temperature as good predictors. In contrast, Upadhyaya et al (2020) emphasized the importance of livestock numbers, ethnic groups, and village distance from the park boundary for explaining livestock losses in Bardia National Park, Nepal. Likewise, Sijapati et al (2021) found that common leopard-induced livestock kills in Bardia National Park were more prevalent at locations distant from the park boundary, subject to seasonality.…”
Section: Discussionmentioning
confidence: 98%
“…Bardia is connected to the Banke National Park to the east and has important corridors that link to forests in the south and the west. Bardia has an elevation range of 150-1,565 m, although about 70% of the park is in the flat lowlands ( Upadhyaya et al, 2020 ). The highway’s ~30 km stretch passes through the Park and bisects its highly productive Karnali River floodplain.…”
Section: Methodsmentioning
confidence: 99%
“…However, the 2021 monsoon season began on 11 June and ended on 16 October ( MoEWRI, 2022 ). The maximum temperature is 45 °C and mean annual rainfall is 1,500 mm ( Dinerstein, 1979 , Upadhyaya et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In Asia, leopards and tigers are among the main predators, which may come into conflict with human activities (e.g. Upadhyaya et al 2020, Shahi et al 2021, Sijapati et al 2021). The range of both species overlaps in Asia (by ~93%), and leopard density may be strongly and negatively affected by tiger density (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Odden et al 2010, Mondal et al 2012, Simcharoen et al 2018), as has their impact on livestock (e.g. Upadhyaya et al 2020, Shahi et al 2021, Sijapati et al 2021), but the factors linked to livestock predation due to their interaction are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%